ANALISIS PENERAPAN METODE PENCATATAN DAN PENILAIAN TERHADAP PERSEDIAAN BARANG DAGANG MENURUT PSAK NO.14 PADA PT. MAYORA INDAH TBK - nurmayanti, risma; Fitriana, Rida; Awaliyah, Salma (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2021)
Inventory is something that is important for the company because with the company's inventory it can maintain its survival and inventory is a large part of the company's activities embedded in the company. The aim of the researcher in conducting this research is to find out whether PT. Mayora Indah Tbk applies the method of recording and valuing merchandise inventory in accordance with PSAK No. 14. PT. Mayora Indah Tbk is a trading company engaged in the manufacture of food, candy and biscuits, and this company sells its products both in domestic and overseas markets. This research was conducted using a qualitative descriptive method and the company carried out a recording method using a perpetual system and a weighted average method. After being analyzed, PT. Mayora Indah Tbk obtained the results that the method of recording and valuing merchandise inventory was in accordance with PSAK No. 14 merchandise inventory.